The Effect Of Risk Management On Listed Indonesian Banking Financial Performance (Period 2019-2023) - Susanto, Andito Wibisono Putra; Setyahuni, Suhita Whini; Subagyo, Herry; Yovita, Lenni; Puspitasari, Diana; Chasanah, Amalia Nur (Indonesia Banking School, 2025)
This study aims to examine the influence of management risks including credit risk, liquidity risk, operational risk, and market risk on banking financial performance. The method used is quantitative with 33 samples of banks listed on the Indonesia Stock Exchange for the period 2019–2023. The sampling technique used purposive sampling. Data analysis was performed by multiple regression using Eviews12 software. The results of the study indicate that market risk (NIM) has a positive effect on (ROA) banking financial performance, while credit risk (NPL), liquidity risk (LDR), and operational risk (BOPO) have a negative effect on (ROA) banking financial performance. The study contributes to the testing of banking risk management using the perspective of agency theory and portfolio theory. The results of this study provide implications for regulators in implementing government policies to help banks reduce risk in improving banking financial performance. Implications for investors in considering and being careful in making investment decisions in banking companies.